Differences in the Effectiveness of Online and Offline Dental and Oral Health Education Management for Middle School Children in the New Normal Era of Covid 19 - Haria Fitri; Eni Rahmi; Nila Kasuma; Murni Wati (Jurnal Kesehatan Gigi, 2022)
Dental and oral health of children in Indonesia is still a problem which is dominated by dental caries and periodontal disease. It is very important to pay attention to the teeth and mouth, otherwise there will be infection and damage to the teeth. Tooth decay in children is also the number one dental problem that occurs among children. The most influential factor in these two diseases is the behavioral factor. Therefore, education about dental and oral health is needed to avoid dental and oral diseases. Through the outreach program, it is hoped that it can increase knowledge and raise awareness of the importance of maintaining dental and oral health and be able to participate actively in improving self-pet efforts. During the Covid-19 pandemic, one must pay attention to dental and oral health. One way to provide education is with an online approach. The purpose of this study was to determine whether there are differences in the effectiveness of online and offline education. This type of research is experimental with a pre-test and post-test group design. Samples were taken by purposive sampling method with a total sample of 250 people. Univariate analysis with N-Gain test, bivariate analysis was performed with Wilcoxon test. The results of this study were equally effective both online and offline with p 0.05Keywords: education ; dental health ; online; offline